ERA DISRUPSI: EKSISTENSI MEDIA PENYIARAN TVRI NTB MELALUI DIVERGENSI MEDIA - Sahril Halim; St. Aisyah; Mohammad Alawi; Najamudin; Lalu Ahmad Zaenuri (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
The era of disruption has transformed the landscape of the television broadcasting industry in Indonesia, forcing it to adapt to the digital ecosystem in order to remain relevant. This study aims to analyze the existence of TVRI NTB in the era of disruption through the processes and forms of media convergence implemented. This study employs a qualitative approach using descriptive methods; data were collected through in-depth interviews, observations, and document analysis conducted with TVRI management, the news department, and the technical department. The results of this study indicate that TVRI NTB utilizes digital multiplatforms to disseminate its broadcast content to reach various age segments. In addition to analog/digital frequencies, TVRI NTB uses platforms such as Live Streaming (YouTube), social media (Instagram, Facebook, TikTok), its website, and the Klik TVRI NTB app. This use of multiplatforms is part of the shifting media consumption culture that continues to be disrupted.  In disseminating content, TVRI NTB uses multiple platforms in accordance with the media divergence model to reach audiences who are not bound by time or place. Despite facing several challenges, TVRI NTB remains capable of maintaining its role as a public broadcasting media. The implementation of adaptive and innovative media divergence strategies is a key factor in maintaining TVRI NTB’s existence amidst the disruption of the broadcasting industry.            Keywords: Disruption, Broadcast Media, TVRI NTB, Divergence.